Енергозаощаджувальний рециклінг псевдосплавів вольфраму - Єрмоленко, Ірина Юріївна; Ведь, Марина Віталіївна; Сахненко, Микола Дмитрович; Богоявленська, Олена Володимирівна (НТУ "ХПІ", 2011)
Pulse galvanostatic polarization was proposed for acceleration of tungsten containing alloys anodic dissolution. A solution composition as well as pulse electrolysis regimes influences both on the anodic dissolution rate and current efficiency was investigated. Optimum electrolysis parameters were determined.
Keywords: тверді промислові відходи; вольфрам; рециклінг; електроліз; анодне розчинення; іонізація